Using the Multicultural and Social Justice Counseling Competencies to Decolonize Counseling Practice: The Important Roles of Theory, Power, and Action. (8th June 2020) - Singh, Anneliese A.; Appling, Brandee; Trepal, Heather
Abstract : The Multicultural and Social Justice Counseling Competencies (MSJCC; Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, 2015) ask counselors to "apply knowledge of multicultural and social justice theories" (p. 8). Counselors who implement the MSJCC in this manner have the opportunity to critically examine traditional counseling theories that were developed within a predominantly White and Western framework, that reproduce North American and European colonist ideology if not contextualized, and that neglect Indigenous approaches to healing (Tuck & Yang, 2012; Watkins & Shulman, 2008). In this article, the authors present 4 key multicultural and social justice theories that can support counselors in adopting a decolonizing paradigm and implementing the MSJCC in their practice with clients: relational‐cultural theory (Miller, 1976), critical race theory (Bell, 1995), intersectionality theory (Crenshaw, 1989, 1991), and liberation psychology (Martín‐Baró, 1994).